Individuals with self-determined motivation for eating have better overall diet quality: Results from the PREDISE study. (1st October 2021) - Carbonneau, Elise; Pelletier, Luc; Bégin, Catherine; Lamarche, Benoît; Bélanger, Mathieu; Provencher, Véronique; Desroches, Sophie; Robitaille, Julie; Vohl, Marie-Claude; Couillard, Charles; Bouchard, Luigi; Houle, Julie; et al.
Abstract: The study aimed at documenting motivational orientations for the regulation of eating as defined by self-determination theory and their association with sociodemographic characteristics and overall diet quality. As part of the PREDISE study, French-speaking women (n = 550) and men (n = 547), aged 18–65 years, living in the Province of Québec, Canada, completed online validated questionnaires. The Regulation of Eating Behavior Scale, based on the self-determination theory, assessed self-determined and non-self-determined motivation to regulate one's eating behavior. Three web-based 24-h food recalls were completed and used to compute the Canadian Healthy Eating Index 2007 (C-HEI), an indicator of the overall adherence to Canadian guidelines for healthy eating. Multiple linear regressions were performed to assess how regulation styles are associated with the C-HEI. Model 1 included no covariate, model 2 included sociodemographic covariates, and fully adjusted model 3 included as covariates sociodemographic variables as well as variables that were previously associated with diet quality, namely nutrition knowledge and social support for healthy eating. Women (p < 0.0001), older individuals (p = 0.0002), those with a higher education level (p < 0.0001), and non-smokers (p < 0.0001) reported higher self-determined motivation score than their counterparts. Self-determined motivation was positively (model 1: B = 4.67, p < 0.0001; model 2: B = 3.82, p < 0.0001; model 3: B = 3.61, p < 0.0001) and non-self-determined motivation was negatively (model 1: B = −1.62, p = 0.0009; model 2: B = −1.63, p = 0.0006; model 2: B = −1.49, p = 0.0022) associated with C-HEI. The present study suggests that some subgroups of the general adult population show more self-determined motivation for eating, which is associated with a better diet quality independently of individual characteristics and other individual and social determinants of healthy eating. Strategies to help individuals internalize the regulation of eating should be further investigated.